Organised labour and the social regulation of global value chains - Lone Riisgaard; Nikolaus Hammer (Danish Institute for International Studies (DIIS), 2008)
Since the 1980s, various processes of economic globalisation have eroded established found-ations of organised labour. The increased mobility of goods and capital, compared to labour's relative immobility, has made it more difficult for labour to advance its objectives through traditional local industrial action or tripartite social contracts. In this paper, we are concerned with the social regulation of global value chains (GVCs) and more specifically the room for manoeuvre that organised labour has for advancing social regulation in different GVCs via Private Social Standards and/ or International Framework Agreements. We argue, that the governance structure (and restructuring) of GVCs frame key elements of the terrain that enables and constrains labour's strategic opportunities for advancing the social regulation of GVCs. Empirically, the paper is based on detailed case studies of the banana and cut flower value chains. Based on the cases we argue, first of all, that a high level of drivenness constitutes a precondition for social regulation along a GVC strand to take place. Secondly, the functional position of the drivers (e.g. producer- and buyer-driven contexts) determines the particular terrains on which contests for the social regulation of GVCs take place and creates different leverage points that may be activated to achieve social regulation. Thirdly, it is historically and locally specific levels of workplace organisation and trade union resources that determine how labour in practice exercises its agency towards social regulation. The reorganisation of GVCs, while seriously constraining some of the more traditional trade union strategies, nevertheless opens new opportunities and new leverage points that can be strategically exploited by labour. The social standard mechanisms reviewed in this paper illustrate some of the new instruments that in addition to other labour strategies constitute potential fruitful avenues in particular GVC terrains.
Keywords: 330; Globalisierung; Betriebliche Wertschöpfung; Internationale Sozialstandards; Gewerkschaftspolitik; Banane; Zierpflanze